The incarceration of Japanese Americans in the 1940s : literature for the high school classroom - Endo, Rachel K. (NCTE high school literature series., 2018)
"Offers texts and activities for teaching about the incarceration of Japanese Americans during World War II, including poems, short stories, and text and film versions of Farewell to Manzanar."--Provided by publisher.